2015
DOI: 10.1111/apa.12870
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of continued playing or singing – from childhood and adolescence to adult years

Abstract: AimMany individuals play an instrument or sing during childhood, but they often stop later in life. This study surveyed adults representative of the Swedish population about musical activities during childhood.MethodsWe asked 3820 adults (65% women) aged from 27 to 54 from the Swedish Twin Registry, who took extra music lessons to those provided at school, to fill in a web‐based questionnaire. Factors analysed were the age they started studying music, the instrument they played, kind of teaching, institution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
(14 reference statements)
3
25
1
1
Order By: Relevance
“…The survey contained a wide range of instruments and questions that took between 55 and 90 min to complete, the procedures of which are further described in Appendix 1.3. Many of these instruments are described in previous publications (e.g., Mosing et al, 2014a , b , 2015 ; Ullén et al, 2014 , 2015 ; Theorell et al, 2015 ). Of these, only auditory SRT, sex, and birth year were utilized in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The survey contained a wide range of instruments and questions that took between 55 and 90 min to complete, the procedures of which are further described in Appendix 1.3. Many of these instruments are described in previous publications (e.g., Mosing et al, 2014a , b , 2015 ; Ullén et al, 2014 , 2015 ; Theorell et al, 2015 ). Of these, only auditory SRT, sex, and birth year were utilized in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Adults who achieve high levels of musical expertise differ from less accomplished musicians in terms of greater levels of passion for music, enhanced music aptitude, and more practice (e.g., Ericsson et al, 1993 ; Ruthsatz et al, 2008 ; Bonneville-Roussy et al, 2011 ; Macnamara et al, 2014 ). In fact, practice is the best predictor that children and adolescents will continue playing music into adulthood (Theorell et al, 2015 ). Practice is also associated with the propensity to experience musical flow, which is defined as being completely absorbed and focused on an activity that one enjoys (Butkovic et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…He found that poor student performance in both sight-reading and in playing by ear were correlated with music lesson dropout rates. Similarly, Theorell et al (2015) found that learning by ear may be significantly and positively associated with continued playing into adulthood.…”
Section: Aural-based Instruction and Delayed Music Readingmentioning
confidence: 90%